Investigating The Globular Cluster System Mass - Halo Mass Relation in High Mass Galaxies - Dornan, Veronika (My University, 2021)
This thesis aims to better constrain the high-mass end of the globular cluster system (GCS) mass - Halo mass relation. This relation between the total mass contained in the globular clusters in a galaxy and the mass of its dark matter halo has been found to be nearly linear. The measured mass ration between the mass of the GCS and the halo mass, defined as eta, has been found to be constant over a large range of galaxy masses, however there is comparatively less data for galaxies with dark matter halo masses >10^13 solar masses. This research analyzes the GCSs of a sample of eleven high-mass brightest cluster galaxies (BCGs) through the use of the photometry program DOLPHOT on Hubble Space Telescope (HST) images in the F814W filter. The mass of the galaxies' GCSs were calculated from their GC radial distributions, and the dark matter halo masses were determined from the known relationship between total stellar mass and halo mass for BCGs. This research utilizes a new standardization technique to calculate the size of the GCS based on the galaxy's virial radius. These GC and halo masses were then compared to determine eta at this high-mass end, which was found to be eta=(6.84+/- 1.47)\times10^-5. When adding the sample BCGs to a catalogue of 303 lower-mass galaxies a total value for eta was found to be eta=(2.99 +/- 0.06)\times10^-5, which is within the literature range for of eta, and is both slightly higher and has a reduced uncertainty compared to the value for the catalogue galaxies alone which was found to be eta=(2.87 +/- 0.11)\times10^-5. This consistency between the eta-values of high-mass and lower-mass galaxies implies that in order for these BCGs to have such massive GCSs, a large proportion of these GCs must be accreted from galaxy mergers at late redshift.
Keywords: astronomy; globular clusters; astrophysics; galaxies